(untitled) (Journal of Fatima Jinnah Medical University, 2018)
Nasal obstruction is the most common complaint in ENT practice. Deviated Nasal Septum (DNS) is the most common cause of nasal obstruction. Septoplasty for symptomatic deviated septum is the commonest nasal surgery performed all over the world. Post septoplasty nasal packing is the most unwanted and unpleasant step in this manouvre. Its use has been proposed to serve multiple purposes as bleeding, heamatoma formation and stabilization of the remaining septal cartilage. But evidence supporting this assertion is limited at best. Various materials are used for nasal packing. Duration of Study: January 2008-January 201 Patients And Methods: A total of 95 patients were included in this study with moderate to marked deviated nasal septum. All patients underwent Septoplasty under G/A with placement of a Quilting Suture with 3/0 vicryl and no nasal packing. Results: Eighty Two (86.32%) patients had no problem. Thirteen (13.68%) patients reported with nasal bleeding who were treated with nasal packs.